Correlation between oral health and severity of respiratory coronavirus infection COVID-19 - A. V. Mitronin; N. A. Apresian; D. A. Ostanina; E. D. Yurtseva (Эндодонтия Today, 2021)
Aim. To establish the association between the presence of chronic infection in oral cavity and the severity of SARSCoV-2 infection.Materials and methods. The study was conducted among 30 people aged between18 and 22 who had had coronavirus infection from mild to severe cases. The assessment of oral health was carried out with main and additional examination methods, CFE index, PMA index, Greene, Wermillion oral hygiene index.Results. In group 1, the average value of CFE index was 4.2, in the second group – CFE index was twice higher at 7.8. PMA index in patients of group 2 was significantly higher (p> 0.01) and was at the level of 41.5%. In group 1, the PMA index was 13.3%. It was found that 17% of the respondents in the control group and 70% patients in the experimental group had an episodic exacerbation of dental diseases during COVID-19.Conclusions. The data obtained indicates a correlation between oral diseases and the severity of COVID-19. It is necessary to consider that chronic infection in the oral cavity as well as poor oral hygiene can act as a risk of complications of viral infections, in particular, of COVID-19.